The Impact of Parental Presence Restrictions on Canadian Parents in the NICU During COVID-19: A National Survey. (February 2023) - Campbell-Yeo, Marsha; Dol, Justine; McCulloch, Holly; Hughes, Brianna; Hundert, Amos; Bacchini, Fabiana; Whitehead, Leah; Afifi, Jehier; Alcock, Lynsey; Bishop, Tanya; Dorling, Jon; Earle, Rebecca; et al.
The purpose of this research was to explore parental perspectives on the impact of parent restrictions imposed in response to the COVID-19 pandemic across Canadian Neonatal Intensive Care Units (NICUs). A co-designed online survey was conducted targeting parents ( n = 235) of infants admitted to a Canadian NICU from March 1, 2020, until March 5, 2021. Parents completed the survey from 38 Canadian NICUs. Large variation in the severity of policies regarding parental presence was reported. Most respondents (68.9%) were classified as experiencing high restrictions, with one or no support people allowed in the NICU, and felt that policies were less easy to understand, felt less valued and respected, and found it more challenging to access medicine or health care. Parents reported gaps in care related to self-care, accessibility, and mental health outcomes. There is significant variation in parental restrictions implemented across Canadian NICUs. National guidelines are needed to support consistent and equitable care practices.